Variation in the topography of the speech production cortex verified by cortical stimulation and high gamma activity - Babajani-Feremi, Abbas (Neuroreport, 2014)
In this study, we have addressed the question of functional brain reorganization for language in the presence and absence of anatomical lesions in two patients with epilepsy using cortical stimulation mapping and high gamma (HG) activity in subdural grid recordings. In both, the expressive language cortex was defined as the cortical patch below the electrode(s) that when stimulated resulted in speech arrest, and during speech expression tasks generated HG activity. This patch fell within the borders of Broca’s area, as defined anatomically, in the case of the patient with a lesion, but outside that area in the other, lesion-free patient. Such results highlight the necessity for presurgical language mapping in all cases of surgery involving the language-dominant hemisphere and suggest that HG activity during expressive language tasks can be informative and helpful in conjunction with cortical stimulation mapping for expressive language mapping.